Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s40834-021-00154-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between media exposure and family planning in Myanmar and Philippines: evidence from nationally representative survey data

Abstract: Background Although women in South Asia and South-east Asia have developed their knowledge regarding modern contraceptive and other family planning techniques, limited information exists on the influence of mass media exposure on the utilization of contraceptives and family planning. The current study examined the association between media exposure and family planning in Myanmar and Philippines. Methods The study analyzed data from the 2017 Philipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
4
8
0
1
Order By: Relevance
“…Findings envisage that the average conceptive use among women of reproductive age who are exposed to FPM significantly increased as compared with those who are not exposed. This finding corroborates the findings that exposure to FPM enhances the use of CU among reproductive-age women 30 .…”
Section: Discussionsupporting
confidence: 90%
“…Findings envisage that the average conceptive use among women of reproductive age who are exposed to FPM significantly increased as compared with those who are not exposed. This finding corroborates the findings that exposure to FPM enhances the use of CU among reproductive-age women 30 .…”
Section: Discussionsupporting
confidence: 90%
“…The final report of this study indicated that having mass media exposure to family planning messages had a significant association with contraceptive utilization. This is consistent with pooled reports in Sub Sahara African countries [ 45 ], and the Philippines [ 46 ]. This might be related to the mass media message about family planning having a significant effect on endorsing and validating negative attitudes about the lesser side effects, issues, and myths of contraceptive use.…”
Section: Discussionsupporting
confidence: 92%
“…This nding corroborates the ndings that exposure to FPM enhances the use of CU among reproductive-age women. 30 Our study has provided empirical evidence to support the incessant calls for policymakers, external donor funding agencies, Civil Society and NGOs to prioritize and increase the resources for implementing family planning communication interventions in low-and middle-income countries. We proposed diverse country-speci c policies, programs, and interventions that incorporate the different dynamics of socio-political, cultural, and other contextual factors that hinder access to family planning messages and the use of contraceptives in SSA.…”
Section: Discussionmentioning
confidence: 74%